Empires of medieval West Africa Ghana, Mali, and Songhay - Conrad, David C. (Chelsea Hourse Publishers, 2010)
This book examines the history and culture of three West African medieval empires; the Ghana, the Mali, and the Songhay through text and illustrations.
Includes bibliographical references and index
Keywords: Geschichte; Soninke (African people) -- History -- Juvenile literature; Mandingo (African people) -- History -- Juvenile literature; Ethnology -- Africa, West -- History -- Juvenile literature; Königreich; Afrika; Ghana (Empire) -- History -- Juvenile literature; Mali (Empire) -- History -- Juvenile literature; Songhai Empire -- History -- Juvenile literature; Africa, West -- History -- To 1884 -- Juvenile literature; Africa -- History -- To 1498 -- Juvenile literature; Westafrika